Scheme of arrangement pursuant to Section 176 of the Malaysia Companies Act 1965 / Zaid Kader Shah - Kader Shah, Zaid (Faculty of Accountancy, 1991)
In the process of carrying out the study, limited articles and studies by specialists especially on the realities of the business and financial environment of Malaysia and compiling the information gathered in a logical order to form this paper delays the completion of this project paper. However with extraction from foreign manuals and academic texts and also advice from the practising professionals while conducting the interviews, this paper is made possible. Methods and procedures done by way of interviewing and discussing with academicians and professionals in position to comment authoritatively on the problems involved and relying on secondary data i.e. published materials and journals as guidelines. In Malaysia, scheme of arrangement is still very new and most of our precedent cases are the English cases relating to this scheme. Initially, an informal scheme will be introduced, perhaps, with full co-operation from all parties involved. Basically it is done by way of written agreement with good relationship of trust between management and creditors whereby the creditor agrees to accept the expected fruits of the scheme in consideration for the deferred repayment of the debt.